Assessment of impact of a control die on marginal fidelity of milled zirconia crown copings for finishing and polishing - Al Akkad, Marwan; Sorensen, John; Hamadah, Omar; Voborna, Iva; Matoušek, Marek; Mounajjed, Radek (Journal of prosthodontics, 2025)
PURPOSE: This study evaluated and compared the marginal fidelity of milled zirconia copings before and after finishing and polishing with and without a control die. MATERIALS AND METHODS: This prospective multicenter in vitro trial involved two methods regularly used in two clinics for hybrid and full-digital workflows. A typodont mandibular molar was prepared. From each workflow, 20 zirconia crown copings were milled from a single scan. Ten zirconia crown copings were assigned randomly from each workflow to be finished and polished. Finishing and polishing in the hybrid workflow were done directly on the typodont, representing the control die. There were four groups in this study: No-die-Before (full-digital without finishing and polishing), No-die-After (hybrid without finishing and polishing), Die-based-Before (full-digital with finishing and polishing), and Die-based-After (hybrid with finishing and polishing). The typodont tooth was divided into eight zones for systematic measurement. All groups were evaluated using a digital optical microscope. RESULTS: The mean values with the standard deviation of No-die-Before, No-die-After, Die-based-Before, and Die-based-After groups were 24.90 ± 23.88, 30.62 ± 32.63, 21.03 ± 16.65, and 18.93 ± 18.27, respectively. The maximum values for the No-die-Before and No-die-After groups were 124 and 131 µm, respectively. All the values in the Die-based-Before and Die-based-After groups were less than the acceptable marginal gap of 75 µm. CONCLUSIONS: There was no statistical significance between the two workflows. However, the control die enabled achieving superior accuracy. Without it, the marginal gap might worsen after finishing and polishing in the full-digital workflow.
Keywords: 3D printing; CAD‐CAM; dental crowns; dental marginal adaptation; prosthodontics; dental prosthesis design